Development of CORE-based Electronic-modules to Improve Students' Problem-Solving Skills - Adam Malik; Muhammad Algi Al-Hanafi; Muhammad Minan Chusni; Andi Rohendi Nugraha (Jurnal Penelitian Pendidikan IPA, 2023)
Students must be trained and develop problem-solving skills as part of 21st-century skills. The study aims to determine the feasibility and implementation of learning CORE-based Electronic-modules and the improvement of students' problem-solving skills on impulse-momentum material. The research method used is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is a validation sheet (expert of material and media and teachers), student worksheets, and tests. The results show CORE-based Electronic-modules after validation an average feasibility of 80% and the implementation of learning activities using CORE-based Electronic-modules an average of 84% including in the very good category. Student worksheets with an implementation percentage of 81% with effective criteria Enhancing students' problem-solving skills of 0.64 with moderate interpretation. The results of hypothesis testing using a paired obtained a tcount of 31.00 > ttable of 2.04. The results show there are differences in problem-solving skills after the implementation of CORE-based electronic modules. The CORE-based electronic modules are feasible to use in the classroom learning process and can improve students' problem-solving skills on impulse-momentum material